Synthesis of New C2-Symmetric Chiral Benzimidazole Derivatives Having Norbornene/Dibenzobarrelene Skeletons - Capan, Irfan; Servi, Suleyman (Bentham Science Publ Ltd, 2020)
Racemic dicarboxylic acids were synthesized from the Diels-Alder cycloaddition reactions which formed the dibenzobarrelene and norbomene skeletons. The pure enantiomers of these compounds were obtained using brucine as the chiral auxiliary. Novel C-2-symmetric chiral benzimidazole derivatives were synthesized from the reaction of the diaminobenzene and enantiomeric dicarboxylic acids in the presence of boric acid.
Keywords: Norbornene; dibenzobarrelene; guanidine; benzimidazole; chiral resolution